A study on the visual behavior and cognitive preferences of female college students in outdoor campus spaces based on eye-tracking - Fang Wen; WeiFeng Zhang; Xinzheng Wang (Frontiers in Psychology, 2026)
Background As life pressures rise and opportunities to connect with nature decline, mental health is a major concern for Chinese college students, with campus outdoor spaces supporting their well-being. Female students show heightened sensitivity to visual comfort, safety, and usability, frequently using outdoor areas for rest, socializing, and emotional regulation. Given the close link between these spaces and their campus experiences, female students are a key group for assessing campus space quality from a gender-responsive perspective. Methods This study combined eye-tracking technology with subjective evaluations to explore female college students’ visual behavior and spatial cognitive preferences in campus outdoor public spaces. A total of 34 female participants aged 18–23 were recruited, and experiments were carried out at six typical campus outdoor sites under non-direct sunlight conditions. Three types of Areas of Interest (AOIs) and 11 environmental object categories were defined. Wearable eye-trackers synchronously collected visual gaze data, supplemented by questionnaire surveys. With image segmentation and spatial analysis, core eye movement indicators were extracted for quantitative analysis. Main findings The results showed that natural landscape elements, especially trees, obtained the highest visual attention in total fixation duration, fixation count and average fixation duration, while functional facilities such as streetlight and stone table attracted less attention. Multi-functional plaza and campus walkway area achieved higher subjective satisfaction, whereas rest and communication areas had lower scores. Correlation analysis verified that attention to natural elements positively correlated with spatial satisfaction ( r = 0.65, p < 0.001), while excessive gazing at road surface and sign negatively correlated with safety and comfort perceptions ( r = −0.57, p < 0.001). Participants urgently demanded better shading facilities, supporting amenities and clear wayfinding. Implications This study identifies key environmental factors affecting female users’ visual experience and perceived safety, providing empirical evidence for targeted refined design of campus outdoor public spaces for female users.